T cells in abdominal aortic aneurysm: immunomodulation and clinical application - Gong, Wei; Tian, Yu; Li, Lei (Frontiers in Immunology, 2023)
Abdominal aortic aneurysm (AAA) is characterized by inflammatory cell infiltration, extracellular matrix (ECM) degradation, and vascular smooth muscle cell (SMC) dysfunction. The inflammatory cells involved in AAA mainly include immune cells including macrophages, neutrophils, T-lymphocytes and B lymphocytes and endothelial cells. As the blood vessel wall expands, more and more lymphocytes infiltrate into the outer membrane. It was found that more than 50% of lymphocytes in AAA tissues were CD3 + T cells, including CD4 + , CD8 + T cells, γδ T cells and regulatory T cells (Tregs). Due to the important role of T cells in inflammatory response, an increasing number of researchers have paid attention to the role of T cells in AAA and dug into the relevant mechanism. Therefore, this paper focuses on reviewing the immunoregulatory role of T cells in AAA and their role in immunotherapy, seeking potential targets for immunotherapy and putting forward future research directions.